Chemical Equilibrium-Based Mechanism for the Electrochemical Reduction of DNA-Bound Methylene Blue Explains Double Redox Waves in Voltammetry - Mahlum, J. D; Pellitero, Miguel Aller; Arroyo-Currás, Netzahualcóyotl (Journal of physical chemistry. C, 2021)
Methylene blue is widely used as a redox reporter in DNA-based electrochemical sensors and, in particular, it is the benchmark DNA-bound reporter used in electrochemical, aptamer-based sensors (E-ABs). Our group recently published an approach to interrogate E-ABs via cyclic voltammetry, which uses the cathodic to anodic peak-to-peak voltage separation (ΔE P) from methylene blue to report on the electron-transfer kinetics and binding state of these sensors. Although effective at scanning rates ≤10 V·s–1, the method is limited at faster scanning rates because cyclic voltammograms of methylene blue-modified, electrode-bound DNA present double faradaic waves that prevent the accurate estimation of ΔE P. These double waves have been observed in previous works, but their origin was unknown. In response, here we investigated the origin of these redox waves by developing a numerical model that incorporates methylene blue’s chemical equilibria in phosphate buffer to predict the shape and magnitude of cyclic voltammograms with 85% or better accuracy from single- and double-stranded DNA. Our model confirms that the peak splitting observed at scanning rates >10 V·s–1 originates from the protonation equilibrium of the radical intermediate species formed after methylene blue receives the first electron. Moreover, the model reveals a strong interaction between the proton transferred during the reduction of methylene blue and the chemical make of blocking self-assembled monolayers typically used in the fabrication of E-ABs. This interaction affects the apparent rate of the first electron-transfer step, accelerating or decelerating it depending on the hydrophobicity and polarity of the blocking monolayer. By expanding our understanding of the effect that monolayer chemistries have on methylene blue’s protonation rates and E-AB signaling, this work may serve the rational design of future sensors with tunable electron-transfer kinetics.